STRATEGI PENGEMBANGAN LAHAN PEKARANGAN PROGRAM RUMAH PANGAN LESTARI (RPL) DALAM MENUNJANG KETAHANAN PANGAN DI KELURAHAN SEPE’E KECAMATAN BARRU KABUPATEN BARRU - Hamisah Hamisah; Ida Rosada; suraedah Alimuddin (Percetakan Umi Toaha Makassar, 2022)
The purpose of this study was to analyze the strategy of developing yard land with the Sustainable Food House system in order to support food security. This research was conducted in the form of a survey in Sepe'e Village, Barru District, Barru Regency. The population in this study were all members of the women's farmer group who participated in the KRPL (Sustainable Food House Area) program in Sepe'e Village, Barru District, Barru Regency, which consisted of 87 members, for a total of 4 women's farmer groups. While the sample in this study is the entire population, namely four groups of women farmers (KWT), The sources of data used in this study were two types of data, namely primary data and secondary data. This research was conducted using data collection techniques, namely interviews, observations, and documentation studies. Data analysis using SWOT analysis. The analysis is carried out to maximize strengths and opportunities and minimize weaknesses and threats. The results of the study: increase public awareness of the potential of home gardens owned by KWT members; maximize the PKRL program launched by the government and utilize available seeds and a supportive climate; create effective marketing channels for home garden products; provide counseling and training to members of KWT regarding good cultivation techniques for home gardens; create market access for home garden products produced by KWT members; conduct counseling on pests and diseases; and utilize technology